LEXICO-SEMANTIC FEATURES OF MODAL VERBS IN FAIRY-TALES (ON THE EXAMPLE OF ENGLISH AND UZBEK FAIRY-TALES) - Sanaqulova Mohinur Omonqul qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The general concept of modality is deeply rooted in philosophy. This idea refers to the interaction between the world and its comprehensive expression. Since language is a means of expressing modality, both linguists and philosophers of language have paid serious attention to this issue. The main focus of the research is on the extremely broad category of modality in linguistics, which reflects different aspects of communication. In this study, the lexical-semantic features of modal verbs in fairy tales (in the case of English and Uzbek fairy tales) are studied.